Synthesis facilitates an understanding of the structural basis for translation inhibition by the lissoclimides - Könst, Zef A.; Szklarski, Anne R.; Pellegrino, Simone; Michalak, Sharon E.; Meyer, Mélanie; Zanette, Camila; Cencic, Regina; Nam, Sangkil; Voora, Vamsee K.; Horne, David A.; Pelletier, Jerry; Mobley, David L.; et al. (Nature chemistry, 2017)
The lissoclimides are unusual succinimide-containing labdane diterpenoids that were reported to be potent cytotoxins. Our short semisynthesis and analogue-oriented synthesis approaches provide a series of lissoclimide natural products and analogues that expand the structure–activity relationships (SARs) in this family. The semisynthesis approach yielded significant quantities of chlorolissoclimide (CL) to permit an evaluation against the National Cancer Institute's 60-cell line panel and allowed us to obtain an X-ray co-crystal structure of the synthetic secondary metabolite with the eukaryotic 80S ribosome. Although it shares a binding site with other imide-based natural product translation inhibitors, CL engages in a particularly interesting and novel face-on halogen– π interaction between the ligand's alkyl chloride and a guanine residue. Our analogue-oriented synthesis provides many more lissoclimide compounds, which were tested against aggressive human cancer cell lines and for protein synthesis inhibitory activity. Finally, computational modelling was used to explain the SARs of certain key compounds and set the stage for the structure-guided design of better translation inhibitors. Several natural and unnatural lissoclimide cytotoxins have been prepared via semi-synthesis and total synthesis. An X-ray co-crystal structure of chlorolissoclimide with the ribosome and evaluation of cytotoxicity and translation inhibition of new compounds in the series improves our understanding of the molecular basis for cytotoxicity.